Mortality Risk Factors Among Patients With Cirrhosis and a Low Model for End‐Stage Liver Disease Sodium Score (≤15): An Analysis of Liver Transplant Allocation Policy Using Aggregated Electronic Health Record Data. Issue 9 (4th April 2017) - Atiemo, K.; Skaro, A.; Maddur, H.; Zhao, L.; Montag, S.; VanWagner, L.; Goel, S.; Kho, A.; Ho, B.; Kang, R.; Holl, J. L.; Abecassis, M. M.; et al.
Abstract : Although the Model for End‐Stage Liver Disease sodium (MELD Na) score is now used for liver transplant allocation in the United States, mortality prediction may be underestimated by the score. Using aggregated electronic health record data from 7834 adult patients with cirrhosis, we determined whether the cause of cirrhosis or cirrhosis complications was associated with an increased risk of death among patients with a MELD Na score ≤15 and whether patients with the greatest risk of death could benefit from liver transplantation (LT). Over median follow‐up of 2.3 years, 3715 patients had a maximum MELD Na score ≤15. Overall, 3.4% were waitlisted for LT. Severe hypoalbuminemia, hepatorenal syndrome, and hepatic hydrothorax conferred the greatest risk of death independent of MELD Na score with 1‐year predicted mortality >14%. Approximately 10% possessed these risk factors. Of these high‐risk patients, only 4% were waitlisted for LT, despite no difference in nonliver comorbidities between waitlisted patients and those not listed. In addition, risk factors for death among waitlisted patients were the same as those for patients not waitlisted, although the effect of malnutrition was significantly greater for waitlisted patients (hazard ratio 8.65 [95% CI 2.57–29.11] vs. 1.47 [95% CI 1.08–1.98]). Using the MELD Na score for allocation may continue to limit access to LT. Abstract : An examination of mortality risk factors independent of MELD sodium in a large population of patients with cirrhosis suggests that some patients at high risk of death may have limited access to liver transplantation. O'Grady and Lake comment in their editorial onpage 2238 .